Pharmacokinetics of a Once-Daily extended-release formulation of pramipexole in healthy male volunteers: Three studies - Jenner, Peter; Könen-Bergmann, Michael; Schepers, Cornelia; Haertter, Sebastian (Clinical therapeutics, 2009)
Background: Pramipexole is a dopamine agonist used in the treatment of Parkinson's disease. The currently available immediate-release (IR) formulation is taken orally 3 times daily. Objectives: These studies were conducted to evaluate the pharmacokinetic properties of a variety of prototypes for a once-daily extended-release (ER) formulation of pramipexole and to further characterize the prototype whose pharmacokinetics best matched those of the IR formulation. Methods: Three Phase I studies were conducted, all in healthy adult men aged ≤50 years with a body mass index of 18.5 to 29.9 kg/m 2. In the first study, 7 prototypes of a once-daily ER formulation with various release properties, including rate and pH dependence, were compared with the IR formulation taken 3 times daily to identify the optimal pharmacokinetic resemblance based on predefined criteria derived from plasma AUC 0−24h, C max, and C min. In the second study, a level A in vitro/in vivo correlation (IVIVC) suitable for predicting an entire in vivo bioavailability time course based on in vitro dissolution was established and validated, and the single-dose pharmacokinetics of the optimal ER formulation identified in the first study were analyzed for food effect. In the third study, steady-state pharmacokinetics of the optimal ER formulation were assessed across a range of pramipexole doses (0.375–4.5 mg/d), including investigation of the food effect at steady state for the highest dose. Tolerability was assessed throughout all studies based on physical examinations, laboratory measurements, and adverse events (AEs). Results: The 3 studies included 18, 15, and 39 subjects, respectively. Among the ER prototypes tested at 0.75 mg once daily in study 1, a matrix tablet had the optimal pharmacokinetic resemblance to IR pramipexole 0.25 mg TID, with a geometric mean AUC 0−24h,ss of 17.4 ng·h/mL (vs 16.0 ng·h/mL for the IR formulation), C max,ss of 0.967 ng/mL (vs 1.09 ng/mL), and C min,ss of 0.455 ng/mL (vs 0.383 ng/mL). For single-dose ER 0.375 mg administered in the fasted state in study 2, in vivo bioavailability was predictable from in vitro dissolution data, with internal mean absolute percent prediction errors of 3.18% for AUC 0−30h and 4.87% for C max, and external mean absolute prediction errors of 6.61% and 3.34%, respectively, satisfying current guidelines for a level A IVIVC. For single-dose ER 0.375 mg administered in the fed state, the upper bound of the 90% CI for fed:fasted values was 119.8 for AUC 0–30h (within the bioequivalence limits of 80%–125%) and 134.1 for C max. At steady state in study 3 (subjects' 5th treatment day), dosing at 0.375 to 4.5 mg in the fasted state was associated with a linear, dose-proportional increase in pharmacokinetic parameters, including AUC 0–24h,ss and C max,ss. At the highest fasted dose (4.5 mg), the geometric coefficient of variation for interindividual variability at steady state was 30.1% for AUC 0–24h,ss (vs 21.4% for IR pramipexole 1.5 mg TID) and 22.3% for C max,ss (vs 19.0%). At steady state, the upper bounds of the 90% CIs for fed:fasted values with ER 4.5 mg were 122.1 for AUC 0–24h and 126.8 for C max. No serious AEs occurred, and the dropout rate was low. Conclusions: In these studies in healthy male volunteers, an ER pramipexole formulation was identified that resembled the IR formulation in terms of both pharmacokinetics and tolerability. In patients with Parkinson's disease, once-daily use of an ER formulation may improve the convenience of treatment relative to the IR formulation taken 3 times daily and thus increase compliance.